ANALISIS RENCANA KERJA PEMERINTAH (RKP) DESA GADING WATU KECAMATAN MENGANTI KABUPATEN GRESIK TAHUN 2022 - Pratama, Dimas Ivan Cahilla; Ma'ruf, Muhammad Farid (Publika, 2023)
Development is a deliberate effort in the framework of change for the better. Within the scope of village government, development must be planned systematically and followed by good governance. In this case, the Village Government Work Plan (RKP) forms the basis for all planning documents, village, sub-district and SKPD development plans at the district, provincial and central government levels. Gading Watu Village, Gresik Regency is one of the independent villages that has made RKPDes with focus on village infrastructure development. However, the preparation has not been carried out optimally, especially on meeting participation and a selective perspective that not all aspirations from the community are accepted. Therefore, the purpose of this research is to analyze the development planning of the Village Government Work Plan (RKPDes) in Gading Watu Village, Menganti District, Gresik Regency. The method used is descriptive qualitative. The research focuses on the theory of village development planning from Ariadi (2019). The subject of this research was determined by purposive sampling technique. Data collection techniques were carried out through observation, interviews and documentation which were then analyzed using data analysis according to Creswell (2014). The results of this study indicate that in the participatory aspect, Gading Watu Village has involved all elements (apparatus, BPD and community) to prepare the RKPDesa. In the aspect of transparency, this is realized through holding village meetings, using the website and displaying banners. In the selective aspect, it has set priorities for physical and non-physical development. The accountable aspect is manifested through musrenbang activities, budget development and implementation. Aspect of empowerment is realized through efforts to improve the skills of the community in trading. As well as aspects of sustainability realized through the implementation of regular evaluation meetings. Keywords: Analysis, Village Government Work Plan (RKPDes), Development.